Biological Roles and Therapeutic Potential of Hydroxy-Carboxylic Acid Receptors - Ahmed, Kashan (Frontiers in Endocrinology, 2011)
In the recent past, deorphanization studies have described intermediates of energy metabolism to activate G protein-coupled receptors and to thereby regulate metabolic functions. GPR81, GPR109A, and GPR109B, formerly known as the nicotinic acid receptor family, are encoded by clustered genes and share a high degree of sequence homology. Recently, hydroxy-carboxylic acids were identified as endogenous ligands of GPR81, GPR109A, and GPR109B, and therefore these receptors have been placed into a novel receptor family of hydroxy-carboxylic acid (HCA) receptors. The HCA1 receptor (GPR81) is activated by the glycolytic metabolite 2-hydroxy-propionic acid (lactate), the HCA2 receptor is activated by the ketone body 3-hydroxy-butyric acid, and the HCA3 receptor (GPR109B) is a receptor for the β-oxidation intermediate 3-hydroxy-octanoic acid. While HCA1 and HCA2 receptors are present in most mammalian species, the HCA3 receptor is exclusively found in humans and higher primates. HCA receptors are expressed in adipose tissue and mediate anti-lipolytic effects in adipocytes through Gi-type G protein-dependent inhibition of adenylyl cyclase. HCA2 and HCA3 inhibit lipolysis during conditions of increased β-oxidation such as prolonged fasting, whereas HCA1 mediates the anti-lipolytic effects of insulin in the fed state. As HCA2 is a receptor for the established anti-dyslipidemic drug nicotinic acid, HCA1 and HCA3 also represent promising drug targets and several synthetic ligands for HCA receptors have been developed. In this article, we will summarize the deorphanization and pharmacological characterization of HCA receptors. Moreover, we will discuss recent progress in elucidating the physiological and pathophysiological role to further evaluate the therapeutic potential of the HCA receptor family for the treatment of metabolic disease.